Effect of exports and development spending on Indonesia's economic growth - Jumiana Jumiana (Digital Business: Tren Bisnis Masa Depan, 2022)
Economic growth is a significant increase in national income within a certain calculation period. This thesis entitled "The Influence of Exports and Development Expenditures on Indonesia's Economic Growth in the 2003-2012 Period" secondary 10-year time series data between 2003-2012. Data were obtained from various sources, including the Central Bureau of Statistics (BPS), and scientific journals and other literature related to this research topic. The analytical method used in this study is multiple regression analysis which is used to determine the magnitude of the effect of changing one variable on another variable with the help of SPSS 17. From the regression results above the R squared (R2) value is 0.957, this means 95.7% variation changes in economic growth variables can be explained simultaneously by variations in export and development expenditure variables, the remaining 4.3% is determined by other variables or factors outside the model. For exports, the results of the study show a significance value lower than the significant level (0.000 <0.05) so that Ho is rejected, Ha is accepted, thus exports have a positive and significant effect on economic growth. While development expenditure, the significant value is greater than the significance level (0.251 > 0.05) so that Ho is accepted Ha is rejected. Thus the results of the study show that the coefficient of development expenditure (X2) is not significant to Indonesia's economic growth.